Telocytes role during the postnatal development of the Mongolian gerbil jejunum - Zani, Bruno C. [UNESP]; Sanches, Bruno D.A.; Maldarine, Juliana S.; Biancardi, Manoel F.; Santos, Fernanda C.A.; Barquilha, Caroline N. [UNESP]; Zucão, Mariele I. [UNESP]; Baraldi, Carolina M.B. [UNESP]; Felisbino, Sergio L. [UNESP]; Góes, Rejane M. [UNESP]; Vilamaior, Patricia S.L. [UNESP]; Taboga, Sebastião R. [UNESP] (Elsevier, 2018)
Telocytes are recently categorised CD34-positive interstitial cells that comprise the cells which were previously called interstitial Cajal-like cells (ICLCs). These were detected in the stroma of various organs such as the prostate, lungs, mammary glands, liver, gallbladder, and jejunum, among others. Several functions have been proposed for telocytes, such as a supportive role in smooth muscle contraction and immune function in adult organs, and tissue organisation and paracrine signalling during development, as well as others. In the jejunum, little is known about the function of telocytes in the adult organ, or is there any information about when these cells develop or if they could have an auxiliary role in the development of the jejunum. The present study employed histological, immunohistochemical and immunofluorescence techniques on histological sections of the jejunum of Mongolian gerbil pups on two different days of postnatal development of the jejunum, covering the maturation period of the organ. By immunolabelling for CD34, it was observed that telocytes are already present in the jejunum during the first week of postnatal life and exist in close association with the developing muscularis mucosae, which are therefore TGFβ1-positive. The telocytes are still present at the end of the first month of life, and a portion of them present co-localisation with c-Kit. Fibroblast-like cells, which are exclusively c-Kit-positive, are also observed, which may indicate the presence of interstitial Cajal cells (ICCs). Finally, it can be hypothesised that a portion of the telocytes may give rise to ICCs, which are c-Kit-positive but CD34 negative.
Keywords: C-kit; CD34; Differentiation; Muscularis mucosae; Telocytes; Weaning